Do drinking motives distinguish extreme drinking college students from their peers?. (September 2016) - White, Helene R.; Anderson, Kristen G.; Ray, Anne E.; Mun, Eun-Young
Abstract: Objective: The literature highlights the need to move beyond the traditional heavy episodic ("binge") drinking criteria when trying to identify at-risk college drinkers. Thus, recent attention has focused on more extreme levels of drinking. This study examines whether drinking motives can distinguish college student extreme drinkers from lighter drinkers. Method: We used data from 3518 college student current drinkers (63.4% women) who participated in eight different studies at five different college campuses across the United States; a subsample of these students was followed up at 6 months post-baseline. At baseline and follow-up, drinkers were divided into three groups: nonbinge drinkers (< 4 drinks for women and 5 for men on their maximum drinking occasion), binge drinkers (4–7 drinks for women; 5–9 for men), and extreme drinkers (8+ for women and 10+ for men). Results: At baseline, extreme drinkers, compared to nonbinge and binge drinkers, reported greater social, enhancement, and coping motives, as well as greater quantity and frequency of drinking per week and more alcohol-related problems. Those who were not extreme drinkers at baseline and later became extreme drinkers at follow-up reported significantly greater increases in social and enhancement motives, compared to those who remained nonextreme drinkers. Those who were extreme drinkers at baseline and reduced their drinking 6 months later, compared to those who remained extreme drinkers, reported greater reductions in enhancement and coping motives. Conclusions: Focusing on drinking motives might be an efficacious target for preventive intervention programs to reduce extreme drinking among college students. Highlights: College extreme drinkers report highest social, enhancement, and coping motives. Students who become extreme drinkers increase their social and enhancement motives. Students who stop extreme drinking decrease their enhancement and coping motives.